LEST WE FORGET: INHUMANITY THREATS IN TEACHING IN THE NEW ERA - Dewi, Novita (LLT Journal: A Journal on Language and Language Teaching, 2021)
Since the prolonged pandemic, teaching language will never be the same even in the New Normal when less strict social distancing measures apply. The sudden shift from offline and/or blended learning to full online learning has brought about diverse pedagogical implications. On the one hand, unlike in traditional teaching and learning, one positive outcome in online learning is the enhancement of social engagement, autonomy, and digital compassion. On the other hand, ignorance, over-indulgence, and cold-heartedness are among the drawbacks of technology-mediated teaching. Drawing from personal experiences and relevant studies, this article highlights the threats of inhumanity when the power of technology takes over life skills that language learners need to acquire. At the core of the recommendation made herein is an open heart in this nearly closed world – a small fraction of Pope Francis’ newest encyclical letter Fratelli Tutti on fraternity and social friendship. The four core values suggested include critical thinking, ethical reasoning, interpersonal connectivity, and compassion.